Challenges and applications to operando and in situ TEM imaging and spectroscopic capabilities in a cryogenic temperature range - Tyukalova, Elizaveta (2022)
Conspectus: In this Account, we describe the challenges and promising applications of transmission electron microscopy (TEM) imaging and spectroscopy at cryogenic temperatures. Our work focuses on two areas of application: the delay of electron-beam-induced degradation and following low-temperature phenomena in a continuous and variable temperature range. For the former, we present a study of LiMn1.5Ni0.5O4 lithium ion battery cathode material that undergoes electron beam-induced degradation when studied at room temperature by TEM. Cryogenic imaging reveals the true structure of LiMn1.5Ni0.5O4 nanoparticles in their discharged state. Improved stability under electron beam irradiation was confirmed by following the evolution of the O K-edge fine structure by electron energy-loss spectroscopy. Our results demonstrate that the effect of radiation damage on discharged LiMn1.5Ni0.5O4 was previously underestimated and that atomic-resolution imaging at cryogenic temperature has a potential to be generalized to most of the Li-based materials and beyond. For the latter, we present two studies in the imaging of low-temperature phenomena on the local scale, namely, the evolution of ferroelectric and ferromagnetic domains walls, in BaTiO3 and Y3Fe5O12 systems, respectively, in a continuous and variable temperature range. Continuous imaging of the phase transition in BaTiO3, a prototypical ferroelectric system, from the low-temperature orthorhombic phase continuously up to the centrosymmetric high-temperature phase is shown to be possible inside a TEM. Similarly, the propagation of domain walls in Y3Fe5O12, a magnetic insulator, is studied from ∼120 to ∼400 K and combined with the application of a magnetic field and electrical current pulses to mimic the operando conditions as in domain wall memory and logic devices for information technology. Such studies are promising for studying the pinning of the ferroelectric and magnetic domains versus temperature, spin-polarized current, and externally applied magnetic field to better manipulate the domain walls. The capability of combining operando TEM stimuli such as current, voltage, and/or magnetic field with in situ TEM imaging in a continuous cryogenic temperature range will allow the uncovering of fundamental phenomena on the nanometer scale. These studies were made possible using a MEMS-based TEM holder that allowed an electron-transparent sample to be transferred and electrically contacted on a MEMS chip. The six-contact double-tilt holder allows the alignment of the specimen into its zone axis while simultaneously using four electrical contacts to regulate the temperature and two contacts to apply the electrical stimuli, i.e., operando TEM imaging. This Account leads to the demonstration of (i) the high-resolution imaging and spectroscopy of nanoparticles oriented in the desired [110] zone-axis direction at cryogenic temperatures to mitigate the electron beam degradation, (ii) imaging of low-temperature transitions with accurate and continuous control of the temperature that allowed single-frame observation of the presence of both the orthorhombic and tetragonal phases in the BaTiO3 system, and (iii) magnetic domain wall propagation as a function of temperature, magnetic field, and current pulses (100 ns with a 100 kHz repetition rate) in the Y3Fe5O12 system.